Synthesis and characterization of Beijing grass mediated silver nanoparticles AgNO3 / Nor Syahirah Manhairi, Dr. Ainorkhilah Mahmood and Dr Norain Isa - Manhairi, Nor Syahirah; Mahmood, Ainorkhilah; Isa, Norain (2020)
Biosynthesis of silver nanoparticles appear as a new alternative approach that is important in utilizing the green source of mother earth. The biomediated silver nanoparticles were synthesized using Beijing grass, an attentive plant that were used by ancient people mainly for medication purpose. The Beijing grass extract were made using spray dried Beijing grass powder using hot extraction method. The effect of silver nitrate concentration as precursor and reactant volume ratio on the synthesis of silver nanoparticles were studied. All samples then proceeded to UV-Vis analysis to verify the formation of nanoparticles. The UV-Vis spectra for silver nanoparticles ranging from 390 nm to 470 nm. Generally, as preliminary conformation, the color changes on the solution indicated the formation of the silver nanoparticles. Based on the result obtained, 5 mM of silver nitrate at volume ratio of 5ml: 5ml of silver nitrate to BGE were chosen as the most optimum reaction condition for synthesis of silver nanoparticles. Even though silver nanoparticles have all the benefits, it still poses toxic characteristic as silver nitrate is a hazardous substance. Hence, the toxicity of the silver nanoparticles should be assess first by performing cytotoxic test before proceed to any broad applications. Lastly, in this report, comparative study on cytotoxicity of silver nanoparticles on living cells were emphasized.